2015
DOI: 10.1002/celc.201500315
|View full text |Cite
|
Sign up to set email alerts
|

Polyanilines with Pendant Amino Groups as Electrochemically Active Copolymers at Neutral pH

Abstract: One of the most promising fields of application of polyaniline (PANI)‐based modified electrodes is the construction of biosensors. However, PANI itself is not electroactive in neutral media. This problem can be solved by copolymerization of aniline with other monomers. Herein, we present a study of the electrosynthesis and electrochemical performance of copolymer films of 3‐aminobenzylamine and aniline. These films are both stable and electroactive in acid and neutral media. They can even be employed as mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 64 publications
3
29
0
Order By: Relevance
“…The features due to the presence of the boronic moiety are expected to be at about 900 and 1100 cm ‐1 for the stretching of the B‐F bond and the bending modes of the B‐OH moiety respectively and at about 1330 cm ‐1 for the stretching mode of the B‐O bond . The position of these peaks is within the region of intense peaks of the PANI‐like structure, so their presence was confirmed by comparison of the Raman spectrum of PAPBA with that of PABA (poly(3‐aminobenzylamine)), which is a similar PANI‐like polymer without boronic moieties . Arrows in this figure indicate the position of these bands characteristic of the boronic group.…”
Section: Resultsmentioning
confidence: 75%
“…The features due to the presence of the boronic moiety are expected to be at about 900 and 1100 cm ‐1 for the stretching of the B‐F bond and the bending modes of the B‐OH moiety respectively and at about 1330 cm ‐1 for the stretching mode of the B‐O bond . The position of these peaks is within the region of intense peaks of the PANI‐like structure, so their presence was confirmed by comparison of the Raman spectrum of PAPBA with that of PABA (poly(3‐aminobenzylamine)), which is a similar PANI‐like polymer without boronic moieties . Arrows in this figure indicate the position of these bands characteristic of the boronic group.…”
Section: Resultsmentioning
confidence: 75%
“…The electropolymerization of substituted aniline (ANI) monomers with extra pendant amino group, such as 3‐aminobenzylamine (ABA), constitutes a promising strategy toward synthesis of electrode materials which combines the electrical properties of PANI with the chemical richness of the amino moieties. We have recently shown that stable films of copolymers of ANI and ABA (PABA) can be obtained by cyclic voltammetry in acidic solution and then employed in neutral electrolytes . Compared to PANI, the copolymers present increased electroactivity in neutral solution which made them suitable candidates for electrochemical devices operating under biocompatible conditions, such as biofuel cells .…”
Section: Mass Increments Determined By Qcm For Different Composite Elmentioning
confidence: 99%
“…Details of PABA electrosynthesis on gold electrodes have been presented and discussed in a previous work . Experimental and additional data about electropolymerization, characterization of electroactivity and chemical composition of PABA by X‐ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM) images of modified substrates are presented in the Supporting Information.…”
Section: Mass Increments Determined By Qcm For Different Composite Elmentioning
confidence: 99%
“…The N1s core spectrum level of PABA can be deconvoluted into 5 peaks as previously reported. 23,24 The backbone N atoms are considered to contribute with 4 bands corresponding to the uncharged N species and positive N species from oxidized secondary amines and protonated imine (Fig. 1).…”
Section: Xpsmentioning
confidence: 99%
“…Additionally, PABA also displays enhanced electroactivity in neutral solutions compared with PANI. 23,24 Owing to its improved processability in aqueous solution, PABA seems to be a better candidate than PANI for the preparation of electrostatically-driven complexes with surfactants. On the other hand, the particular interaction between protonated amines and phosphate anions has been extensively recognized.…”
mentioning
confidence: 99%